Utilização de uma ferramenta digital para o ensino de parasitologia no ensino superior - Aranha, Valéria Leite (2019)
This research deals with the use of a digital tool known as Powtoon for the teaching of Parasitology. The present study was carried out in a sample of 150 Biomedicine, Biological Sciences, Pharmacy and Veterinary Medicine courses at the University Centro Nossa Senhora do Patrocínio (CEUNSP), located in the city of Itu and Salto, in the state of São Paulo. The purpose of the study was to use the Powtoon digital tool in the courses of the health area to create parasite prevention campaigns in the discipline of Parasitology. As a guideline, a discriminatory form was drawn up containing evaluation criteria for the presentations of the campaigns, such as: classification of the parasite, life cycle, pathogenesis, prophylaxis and treatment. We used as tools for the evaluation of students' perceptions, semi-structured online questionnaire developed in Google Drive. The results showed that there is a positive correlation in the use of the Powtoon digital tool with teaching, motivation and in the dissemination of health campaigns to prevent parasitosis.